Tropical terrestrial invertebrates—Where to from here?. (30th March 2020) - Dahlsjö, Cecilia A.L.; Eggleton, Paul; Kitching, Roger
Abstract: There are over one million described invertebrate species on Earth, the majority of which are likely to inhabit the highly biodiverse rain forests around the equator. These are some of the most vulnerable ecosystems on Earth due to the pressures of deforestation and climate change with many of their inhabitants at risk of extinction. Invertebrates play a major role in ecosystem functioning from decomposition and nutrient cycling to herbivory and pollination; however, while our understanding of these roles is improving, we are far from being able to predict the consequences of further deforestation, climate change, and biodiversity loss due to the lack of comparative data and the high proportion of species which remain to be discovered. As we move into an era of increased pressure on old‐growth habitats and biodiversity, it is imperative that we understand how changes to invertebrate communities, and the extinction of species, affect ecosystems. Innovative and comprehensive methods that approach these issues are needed. Here, we highlight priorities for future tropical terrestrial invertebrate research such as the efficiency of sustainable land management, exploration of innovative methods for better understanding of invertebrate ecology and behavior, and quantifying the role of invertebrates in ecosystem functioning.